Faith-Based HIV Care and Prevention in Chinese Immigrant Communities: Rhetoric or Reality? - Kang, Ezer (2011)
Ethnic churches attended by first generation Chinese immigrants are uniquely positioned to address emerging HIV prevention and care needs within the Chinese community at-large. Efforts to develop faith-based HIV programs necessitate identifying how HIV intersects with the sinicization of Christianity within Chinese churches. This paper will review the process of contextualizing HIV within theological and cultural frameworks that are meaningful for ethnic Chinese church leaders and members. The authors specifically propose two points of integration between public health and ecclesial functions: (1) HIV stigma-mitigation initiatives as informed by Christo-centric teachings of compassion and justice, and (2) HIV prevention and care reframed as social responsibility and informed by the Christian tradition of evangelism. Systems and practices that hinder and promote the involvement of Chinese churches in HIV prevention, care, and stigma-reduction will be discussed.